(untitled) (Scientific Journal of Research Studies in Future Management, 2024)
The aim of this study was to investigate the effect of charismatic leadership in human resource management. The research method is of an applied type. The statistical population of the study includes all employees of Abrah Tazeen Company, which was determined by simple random method and Cochran formula with a sample size of 341 people. The data collection tool was the Charismatic Leadership Questionnaire by Cho (2020) and the Human Resource Management Questionnaire by Mirspasi (2011). The opinions of experts were used to examine the validity and to determine the reliability, Cronbach's alpha was used. Pearson and Regression tests and SPSS software version 26 were used to analyze the data. The findings showed that charismatic leadership has a positive and direct effect on the dimensions of human resource management, including recruitment and hiring, employment, promotion and retention, and all research hypotheses were confirmed.